Implicit motives predict affective responses to emotional expressions - Rösch, Andreas G.; Stanton, Steven J.; Schultheiss, Oliver C. (Frontiers in Psychology, 2013)
We explored the influence of implicit motives and activity inhibition on subjectively experienced affect in response to the presentation of six different facial expressions of emotion (FEEs; anger, disgust, fear, happiness, sadness, and surprise) and neutral faces from the NimStim set of facial expressions (Tottenham et al., 2009). Implicit motives and activity inhibition were assessed using a Picture Story Exercise (Schultheiss et al., 2009b). Ratings of subjectively experienced affect (arousal and valence) were assessed using Self-Assessment Manikins (Bradley and Lang, 1994) in a sample of 84 participants. We found that people with either a strong implicit power or achievement motive experienced stronger arousal, while people with a strong affiliation motive experienced less aroused and felt more unpleasant across emotions. Additionally, we obtained significant power motive × activity inhibition interactions for arousal ratings in response to FEEs and neutral faces. Participants with a strong power motive and weak activity inhibition experienced stronger arousal after the presentation of neutral faces but no additional increase in arousal after the presentation of FEEs. Participants with a strong power motive and strong activity inhibition (inhibited power motive) did not feel aroused by neutral faces. However, their arousal increased in response to all FEEs with the exception of happy faces, for which their subjective arousal decreased. These more differentiated reaction pattern of individuals with an inhibited power motive suggest that they engage in a more socially adaptive manner of responding to different FEEs. Our findings extend established links between implicit motives and affective processes found at the procedural level to declarative reactions to FEEs. Implications are discussed with respect to dual-process models of motivation and research in motive congruence.